2022
DOI: 10.3390/brainsci12070952
|View full text |Cite
|
Sign up to set email alerts
|

PS-NPs Induced Neurotoxic Effects in SHSY-5Y Cells via Autophagy Activation and Mitochondrial Dysfunction

Abstract: Polystyrene nanoparticles (PS-NPs) are organic pollutants that are widely detected in the environment and organisms, posing potential threats to both ecosystems and human health. PS-NPs have been proven to penetrate the blood–brain barrier and increase the incidence of neurodegenerative diseases. However, information relating to the pathogenic molecular mechanism is still unclear. This study investigated the neurotoxicity and regulatory mechanisms of PS-NPs in human neuroblastoma SHSY-5Y cells. The results sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…MNPs augment neurotoxicity in SHSY-5Y cells through the activation of autophagy and mitochondrial dysfunction, which are modulated by mitochondrial oxidative stress. Hence, mitochondrial damage caused by oxidative stress may be involved in the pathological mechanisms of MNP-evoked neurodegenerative diseases [ 65 ].…”
Section: Toxicities Of Micro- and Nanoplastics On Mitochondriamentioning
confidence: 99%
“…MNPs augment neurotoxicity in SHSY-5Y cells through the activation of autophagy and mitochondrial dysfunction, which are modulated by mitochondrial oxidative stress. Hence, mitochondrial damage caused by oxidative stress may be involved in the pathological mechanisms of MNP-evoked neurodegenerative diseases [ 65 ].…”
Section: Toxicities Of Micro- and Nanoplastics On Mitochondriamentioning
confidence: 99%
“…[127] PS-NPs have been shown to penetrate the blood-brain barrier. Tang et al [128] found that PS-NPs induced ROS production Abbreviations: Akt, protein kinase B; AMPK, AMP-activated protein kinase; CIR NLP, nanoliposomes; CL, cationic liposomes; CSNPs, chitosan nanoparticles; ERK1/2, Extracellular signal-regulated kinase 1/2; JNK, c-Jun amino(N)-terminal kinase; mTOR, mammalian target of rapamycin; NQ, quercetin nanoparticles; PAMAM, polyamidoamine; PBS, phosphate buffered salin; PS-NPs, polystyrene nanoparticles; ROS, reactive oxygen species; TTF1-NPs, 5,2',4'-trihydroxy-6,7,5'-trimethoxyflavone nanoparticle. cannot be ignored.…”
Section: Polystyrene Nanoparticles (Ps-nps)mentioning
confidence: 99%
“…[ 127 ] PS‐NPs have been shown to penetrate the blood‐brain barrier. Tang et al [ 128 ] found that PS‐NPs induced ROS production and mitochondrial damage in SHSY‐5Y cells. NPs‐induced mitochondria‐dependent apoptosis and autophagy could potentially trigger neurodegenerative diseases.…”
Section: Autophagy Regulation By Organic Npsmentioning
confidence: 99%
“…However, exposure to micro-and nanoplastics can disrupt the balance between ROS production and scavenging, leading to ROS overproduction. In addition, micro-and nanoplastics can also lead to the translocation of cytochrome c from mitochondria to the cytoplasm, which can trigger the activation of caspases and the induction of apoptosis [102,103]. The antioxidant defense system plays a critical role in protecting cells against oxidative stress induced by micro-and nanoplastics.…”
Section: Mps/nps' Effects On Phytoplanktonmentioning
confidence: 99%